TRAUMA-INFORMED HERMENEUTICS IN THE CONDITIONS OF COLLECTIVE CRISIS: UKRAINIAN CONTEXT 2022-2025 - Ашихміна, Марина; Абрамов, Максим (SWorldJournal, 2026)
This article addresses the limitations of classical hermeneutics in interpreting traumatic experience under conditions of collective crisis, focusing on the Ukrainian context of Russia’s full-scale war against Ukraine (2022–2025). Classical hermeneutical